Kinetic Profiles and Management of Hepatitis B Virus Reactivation in Patients With Immune‐Mediated Inflammatory Diseases. Issue 9 (26th August 2013) - Droz, Nina; Gilardin, Laurent; Cacoub, Patrice; Berenbaum, Francis; Wendling, Daniel; Godeau, Bertrand; Piette, Anne‐Marie; Dernis, Emmanuelle; Ebbo, Mikael; Fautrel, Bruno; Le Guenno, Guillaume; Mekinian, Arsène; et al.
<x xml:space="preserve">Abstract</x> Objective Immunosuppressive therapy may trigger hepatitis B virus (HBV) reactivation for increased morbidity and mortality. We aimed to describe HBV reactivation in patients receiving treatment for immune‐mediated inflammatory diseases (IMIDs) and to evaluate a predefined algorithm for its prevention. Methods Physicians submitted data for patients receiving treatment for IMIDs and exhibiting HBV reactivation, defined as an increase of >1 log10 IU/ml of HBV DNA levels or DNA reappearance. We systematically reviewed cases in the literature. Results The 35 physician‐collected patients had rheumatoid arthritis (n = 14), connective tissue disease (n = 7), vasculitis (n = 5), and other diseases (n = 9). At baseline, 65.7% of patients were positive for hepatitis B surface antigen (HBsAg), 31.4% had a history of HBV infection, and 2.9% had occult HBV infection. Reactivation occurred a median of 35 weeks (range 2–397 weeks) after the start of corticosteroid and/or immunosuppressive therapy. In all, 88.6% of patients were clinically asymptomatic, but 25.7% had severe hepatitis; none had fulminant hepatitis. Management was antiviral therapy for 91.4%, with discontinuation or decrease of immunosuppressive therapy for 45.7%. In pooling these 35 cases and 103 patients from the literature, 73.9% of patients were clinically asymptomatic, 33.3% had severe hepatitis, and 12.3% died and/or had fulminant hepatitis. Reactivation occurred early with rituximab or cyclophosphamide therapy and in HBsAg‐positive/HBV DNA–positive patients. Using the predefined algorithm, 78% of patients with reactivation would have received preemptive antiviral therapy. Conclusion We provide new insights into HBV reactivation in patients receiving treatment for IMIDs. A predefined algorithm may be effective in reducing the risk of HBV reactivation in this population.